Funkcja 1Hen 9,1-3 w strukturze literackiej mitu o upadłych aniołach 1Hen 6-11 - Domka, Natalia Honorata (The Biblical Annals, 2019)
The article analyses the structure of 1 En. 9:1-3 and its function within the larger structure of the myth of the fallen Watchers (1 En. 6–11). The short text introduces the four angels on the scene, their perception of the miserable state of humanity, and the reception of human complaint directed to God. The positive presentation of the four angels can be contrasted by the negative presentation of the fallen Watchers in 6,2-3.7-8. On the other hand, 1 En. 9:1-3 is related to 1 En 10:1-16 where the same four angels receive from God the divine commissioning. Since it introduces the decisive turn in the myth narrative thread, 1 En 9:1-3 divides the myth into two parts, which implies the symmetric disposition of the myth.